HYDRO-SOCIAL RELATION OF INDIGENOUS RELIGION: BALI AGA - Ahdar, Rozi (NALAR: Jurnal Pendidikan dan Kebudayaan, 2023)
Water management is very influenced by economy or tourism and determined by profit gain. Drought, pollution, and poaching conflict occur which show how people today do not know how to maintain water wisely. On the other hand, people in indigenous villages have ways to maintain quality water. One of it is explored by Ghorbani et al. He explores how indigenous science is applied to create a better water distribution and drought postponement in Jiroft County, Iran. This qualitative paper aims to explain the hydro-social relation of another indigenous religion, it is known as Bali Aga. Supported by literature study, this paper argues that Bali Aga’s religion-based hydro-social relation is effective in water management. This paper contributes to and has implication for water management in other places around the planet.